Apixaban versus PhenpRocoumon: Oral AntiCoagulation plus antiplatelet tHerapy in patients with Acute Coronary Syndrome and Atrial Fibrillation (APPROACH-ACS-AF): Rationale and design of the prospective randomized parallel-group, open-label, blinded-endpoint, superiority, multicenter-trial of a triple therapy versus a dual therapy in patients with Atrial Fibrillation and Acute Coronary Syndrome undergoing coronary stenting. (August 2021) - Riesinger, Lisa; Strobl, Claudia; Leistner, David M.; Gori, Tommaso; Akin, Ibrahim; Mehr, Michael; Kellnar, Antonia; Mahabadi, Amir A.; Bogossian, Harilaos; Block, Michael; Edelmann, Frank; Sarafoff, Nikolaus; et al.
Abstract: Background: A regimen of dual (DAT) vs. triple (TAT) antithrombotic therapy reduces bleeding in patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI). However, recent evidence suggests that DAT may be associated with an increased ischemic risk. This raises the question whether DAT rather than TAT should be recommended to AF patients that undergo PCI for acute coronary syndrome (ACS), carrying a particularly high risk of both bleeding and ischemic events, studied only as subgroups of previous trials. Methods and design: The APPROACH-ACS-AF-(DZHK-7) trial is a multicenter prospective, randomized, open-label, blinded endpoint (PROBE) trial which will include patients presenting with an ACS managed by PCI and requiring oral anticoagulation (OAC) due to AF. The trial will test, whether a DAT-regimen comprising clopidogrel plus the non-Vitamin-K-antagonist oral anticoagulant (NOAC) apixaban is superior to a TAT-regimen of vitamin-K-antagonist (VKA) plus dual anti-platelet therapy (APT) with respect to bleeding. A total of 400 patients will be randomized 1:1 to a control-arm with guideline-recommended TAT with VKA plus clopidogrel and acetylsalicylic-acid and a study arm receiving DAT comprising apixaban plus clopidogrel. Patients will be followed-up for 6 months. The primary endpoint of the study is the cumulative incidence of BARC type ≥2 bleeding, secondary endpoints include a composite clinical ischemic outcome and net clinical outcome. Conclusions: APPROACH-ACS-AF is the first trial dedicated to ACS patients, testing whether in terms of bleeding a DAT with NOAC is superior to a TAT regimen with VKA in high-risk ACS patients with AF.